THE EFFICACY OF INDIRECT CORRECTIVE FEEDBACK IN IMPROVING STUDENTS' WRITING SKILL IN WRITING NARRATIVE TEXTS - Putri, Esti Tri Astuti (2016)
Feedback is an essential element of a process approach to writing. Indirect Corrective Feedback involves indicating that the student has made an error without actually correcting it. This research aims to discover the efficacy of indirect corrective feedback in improving students' writing skill in writing narrative texts. Furthermore, this study was conducted to find out students' responses toward indirect corrective feedback given as treatment. The study implemented a quasi-experimental design. The sample of this study involves 30 students as control group and 30 students as experimental group. Students' writing and questionnaire were used to obtain the data in this study. Afterwards, computational statistical was used in this research. One way analysis of variance test in SPSS 19.0 was conducted to analyze the data. Based on the statistical result, after indirect corrective feedback was implemented on students' writing, the level of significance is .000 or < 0.05, thereby the null hypothesis was rejected. Therefore, the use of indirect corrective feedback improves the writing accuracy in writing narrative text. In addition, from the questionnaires' result show 96 % students gave positive response toward indirect corrective feedback. Keywords: Indirect Corrective Feedback, Writing Skill, Narrative Text. Umpan balik merupakan elemen penting dari pendekatan proses untuk menulis. Indirect Corrective Feedback adalah menunjukkan bahwa siswa telah membuat kesalahan tanpa benar-benar mengoreksinya. Penelitian ini bertujuan untuk mengetahui efektivitas Indirect Corrective Feedback dalam meningkatkan kemampuan menulis siswa dalam menulis teks naratif. Selanjutnya, penelitian ini dilakukan untuk mengetahui tanggapan siswa terhadap umpan balik korektif tidak langsung diberikan sebagai perlakuan. Penelitian ini menerapkan desain kuasi-eksperimental. Sampel penelitian ini melibatkan 30 siswa sebagai kelompok kontrol dan 30 siswa sebagai kelompok eksperimen. Tulisan dan kuesioner siswa digunakan untuk memperoleh data dalam penelitian ini. Setelah itu, komputasi statistik yang digunakan dalam penelitian ini. Salah satu analisis cara uji varians dalam SPSS 19,0 dilakukan untuk menganalisis data. Berdasarkan hasil statistik, setelah Indirect Corrective Feedback dilaksanakan pada tulisan siswa, tingkat signifikansi adalah 0,000 atau <0,05, sehingga hipotesis nol ditolak. Oleh karena itu, penggunaan Indirect Corrective Feedback meningkatkan akurasi menulis dalam menulis narasi teks. Selain itu, dari hasil kuesioner 'menunjukkan 96% siswa memberikan respon positif terhadap Indirect Corrective Feedback. Kata kunci: Indirect Corrective Feedback, Keterampilan menulis, Teks naratif.